Analysis of COVID-19 reinfection and its influencing factors among primary healthcare workers in Jiangsu Province: a study based on the omicron variant epidemic - Fu, Mingwang; Chen, Hualing; Qian, Yongkang; Zhang, Yongjie; Guo, Haijian; Shen, Ya; Xu, Biyun; Han, Wantong; Zhou, Haoran; Xu, Jinshui; Chen, Bingwei (Frontiers in Public Health, 2025)
ObjectivesSince the global outbreak of SARS-CoV-2 in 2019, COVID-19 reinfection has become an increasing concern, particularly during the spread of the Omicron variant. Despite numerous international studies on COVID-19 reinfection, research focusing on healthcare workers, particularly those in primary care settings in mainland China, remains limited. This study aims to evaluate COVID-19 reinfection rates among primary healthcare workers (PHWs) in Jiangsu Province and to explore potential risk factors contributing to reinfection.MethodsThis study utilized a combination of online questionnaires and on-site surveys to conduct two waves of investigation targeting PHWs after epidemic control policy adjustment in Jiangsu Province. Differences between the infection at the baseline visit and re-infection at the follow-up visit were analyzed, and multivariate logistic regression was used to assess the factors influencing reinfection.ResultsA total of 5,541 PHWs were included in the study. At the baseline visit, the initial infection rate was 85.85% [95% confidence interval (CI): 84.93–86.77%], and the self-reported reinfection rate was 40.05% (95% CI: 38.65–41.44%). After adjustment, the reinfection rate was 29.41% (95% CI: 28.12–30.71%). The median reinfection interval between the two infections was 146 days (Interquartile range: 129–164 days). Logistic regression model revealed that female sex [odds ratio (OR) = 1.376, 95% CI: 1.190–1.592], history of fever clinic work (OR = 1.179, 95% CI: 1.045–1.330), working over 8 h per day (OR = 1.178, 95% CI: 1.040–1.336), being a nurse (OR = 1.201, 95% CI: 1.029–1.402), and a “less meat, more vegetables” diet (OR = 1.206, 95% CI: 1.020–1.426) were significant risk factors for reinfection. Additionally, regular physical exercise was found to be a protective factor (OR = 0.861, 95% CI: 0.754–0.983).ConclusionCOVID-19 reinfection rates were relatively high among PHWs in Jiangsu Province, particularly among women, nurses, those with fever clinic experience and working over 8 h per day. This study offers valuable insights for the prevention of COVID-19 reinfection and the development of protection strategies for PHWs. It is recommended that more targeted protective measures be implemented for high-risk groups, including appropriate work arrangements, regular health monitoring, and the promotion of healthy lifestyle habits.